2001
DOI: 10.1046/j.1523-1755.2001.07834.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathionyl hemoglobin in uremic patients undergoing hemodialysis and continuous ambulatory peritoneal dialysis

Abstract: Glutathionyl Hb levels were increased in HD and CAPD patients, probably because of enhanced oxidative stress. The measurement of glutathionyl Hb may be useful to assess oxidative stress in uremic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…We found high levels of HbSSG in cells of HD patients which in addition to being consistent with the parallel observation of diminished GSH/GSSG E h , confirm the presence of oxidative stress and point to an attempt of cell proteins to scavenge low molecular mass disulfides from the cytosol. S -glutathionylation of Hb, a rare event in healthy erythrocytes, 11 was reported in a number of pathologic conditions besides renal failure 2325 including diabetes, hyperlipidemia and Friedreich’s ataxia. 2627, 2823 It is interpreted as a mechanism to regenerate reduced free GSH from disulfide GSSG and, ultimately, as a buffering defense mechanism against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…We found high levels of HbSSG in cells of HD patients which in addition to being consistent with the parallel observation of diminished GSH/GSSG E h , confirm the presence of oxidative stress and point to an attempt of cell proteins to scavenge low molecular mass disulfides from the cytosol. S -glutathionylation of Hb, a rare event in healthy erythrocytes, 11 was reported in a number of pathologic conditions besides renal failure 2325 including diabetes, hyperlipidemia and Friedreich’s ataxia. 2627, 2823 It is interpreted as a mechanism to regenerate reduced free GSH from disulfide GSSG and, ultimately, as a buffering defense mechanism against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathionyl-haemoglobin is increased in patients suffering from type I and type II diabetes, Friedreich's ataxia, hyperlipidemia, and uremia associated with haemodialysis or peritoneal dialysis [20,58,[61][62][63]. Differently, a decrease in the normal (basal) concentration of glutathionylhaemoglobin has been measured in children with Down's syndrome [64].…”
Section: S-glutathionylated Proteins In Human Diseasesmentioning
confidence: 99%
“…Friedreich's ataxia [39,58] Human immunodeficiency virus [52] Hyperlipidemia [61] Renal cell carcinoma [72] Type I diabetes [20,62] Type II diabetes [61] Uremia and hemodialysis or peritoneal dialysis [63] of haemoglobin can exist in human erythrocytes [67]. However, we have shown that inappropriate blood sample manipulation can lead to an artifactual increase in PSSGs, because many variables may affect the PSSG measurement: for instance, used reagents, incubation times with different substances, sample freezing, acid precipitation of proteins [20,40].…”
Section: Disease Referencesmentioning
confidence: 99%
“…In healthy individuals, 1.2-16% of total hemoglobin (35-37) is glutathionylated (although these high estimates have been challenged by ref. 38), and various situations that cause oxidative stress exacerbate glutathionylation (36)(37)(38). The glutathionyl-hemoglobin adduct has lower cooperativity at halfsaturation and has a 4-to 10-fold higher oxygen affinity than hemoglobin A (39), making for poorer oxygen delivery to tissues.…”
Section: Requirement For Low Gssg Concentrations Is Capable Of Mediatmentioning
confidence: 99%